DINAMIKA DAN KEWIRAUSAHAAN SOSIAL MASYARAKAT DESA BICAK, TROWULAN, MOJOKERTO DALAM MENGHADAPI PANDEMI COVID-19 - Anik Susanti; Nyimas Nadya Izana; Hoiril Sabariman (Jurnal Pendidikan Ilmu Sosial, 2022)
The Covid-19 pandemic caused various disturbances in society, especially in the socio-economic field. Almost all residents of Bicak Village feel the impact, this is because most of the residents are engaged in agriculture. The pandemic resulted in reduced grain prices and fewer job opportunities. However, the economy must keep moving by digging in, trying, and revitalizing local potential and resources. This research is based on social entrepreneurship to address the impact of the pandemic. Qualitative approaches with descriptive methods are used to explain the phenomenon of the revitalization of the impact of the pandemic with local potential-based social entrepreneurship. Primary data is collected through observations, interviews, and airy records, while primary data is from various sources of documentation. The results showed that the Bicak Village Government improved the quality of human resources in terms of practically useful knowledge and skills. Such as providing sewing machines to facilitate the creativity of citizens. In addition, the Bicak Village Government proposed training in making crafts from kur yarn. Crafts from kur threads are projected as embryos from a group of business units that the Bicak Village Government plans to shade by BUMDes. Society has a group of craftsmen who have received sewing training. The kur yarn crafting business can be regarded as a trial effort to pioneer small businesses to minimize the impact of the pandemic. The research team held workshops on making innovative model yarn crafts and marketing products online.